Simultaneous vs. sequential treatment for smoking and weight management in tobacco quitlines: 6 and 12 month outcomes from a randomized trial - Terry Bush; Jennifer Lovejoy; Harold Javitz; Alula Jimenez Torres; Ken Wassum; Marcia M. Tan; Bonnie Spring (BMC, 2018)
Abstract Background Smoking cessation often results in weight gain which discourages many smokers from quitting and can increase health risks. Treatments to reduce cessation-related weight gain have been tested in highly controlled trials of in-person treatment, but have never been tested in a real-world setting, which has inhibited dissemination. Methods The Best Quit Study (BQS) is a replication and "real world" translation using telephone delivery of a prior in-person efficacy trial. Design: randomized control trial in a quitline setting. Eligible smokers (n = 2540) were randomized to the standard 5-call quitline intervention or quitline plus simultaneous or sequential weight management. Regression analyses tested effectiveness of treatments on self-reported smoking abstinence and weight change at 6 and 12 months. Results Study enrollees were from 10 commercial employer groups and three state quitlines. Participants were between ages 18-72, 65.8% female, 68.2% white; 23.0% Medicaid-insured, and 76.3% overweight/obese. The follow-up response rate was lower in the simultaneous group than the control group at 6 months (p = 0.01). While a completers analysis of 30-day point prevalence abstinence detected no differences among groups at 6 or 12 months, multiply imputed abstinence showed quit rate differences at 6 months for:simultaneous (40.3%) vs. sequential (48.3%), p = 0.034 and simultaneous vs. control (44.9%), p = 0.043. At 12 months, multiply imputed abstinence, was significantly lower for the simultaneous group (40.7%) vs. control (46.0%), p < 0.05 and vs. sequential (46.3%), p < 0.05. Weight gain at 6 and 12 months was minimal and not different among treatment groups. The sequential group completed fewer total calls (3.75) vs. control (4.16) and vs. simultaneous group (3.83), p = 0.01, and fewer weight calls (0.94) than simultaneous (2.33), p < 0.0001. The number of calls completed predicted 30-day abstinence, p < 0.001, but not weight outcomes. Discussion This study offers a model for evaluating population-level public health interventions conducted in partnership with tobacco quitlines. Conclusions Simultaneous (vs. sequential) delivery of phone/web weight management with cessation treatment in the quitline setting may adversely affect quit rate. Neither a simultaneous nor sequential approach to addressing weight produced any benefit on suppressing weight gain. This study highlights the need and the challenges of testing intensive interventions in real-world settings. Trial registration ClinicalTrials.gov Identifier: NCT01867983. Registered: May 30, 2013.